Design of a Location-Based Monitoring System for Agricultural Extension Officers at the Department of Food Security and Agriculture of Bojonegoro District Using the Waterfall Development Method and Hybrid Application - Fawwaz Ali Akbar; Budi Nugroho; Annisaa Sri Indrawanti (Jurnal Teknologi dan Manajemen, 2024)
The Department of Food Security and Agriculture (DKPP) of Bojonegoro District is a government agency at the district level that focuses on food security and agriculture. The main objective of this department is to enhance the production of food crops, horticulture, and plantations through the improvement of human resources and agricultural infrastructure. DKPP Bojonegoro has undertaken various initiatives to improve the quality and quantity of agricultural products. One of these initiatives involves deploying extension officers to provide guidance and support to farmers in the field, both those formally affiliated with Farmer Groups (POKTAN) and individual farmers. In practice, each extension officer is assigned to a district or the area of a farmer group that requires assistance, with assignments subject to change and flexibility based on the needs of DKPP Bojonegoro. However, the challenge lies in DKPP's difficulty in ensuring that the extension officers are effectively carrying out their duties in the field. The monitoring function performed so far relies solely on reports submitted by the extension officers, a method that may lack validity in verifying whether the officers are performing their tasks well in the field. In response to this issue, the proposed solution in this research is a Location-Based Monitoring System for agricultural extension officers. The goal is to facilitate DKPP in monitoring the presence of extension officers in designated areas and to automatically manage attendance when assigning officers to a farmer group or district.